Welfare Effects of Food Tariff Changes on Urban and Rural Households - Samaneh Khalili Malekshahi; Mohammad Ghahremanzadeh; Azadeh Falsafian (Journal of Agricultural Sciences)
This study aims to analyze the effects of food tariff changes on the welfare of urban and rural households in Iran. The study considers the role of households as consumers, producers, and workers, as well as the market structure over the past fifteen years. Firstly, the study estimated the consumption behavior for the main food groups using the QUAIDS and pseudo-panel data. Then, the extent of tariff pass-through to domestic food prices was determined, and after that, price-wage elasticity and wage changes as a result of tariff changes were estimated. Finally, it calculated the effect of tariff changes on household purchasing power and income through an indirect utility function to get welfare effects. The results indicate that tariff pass-through to food prices is incomplete and varies between urban and rural areas. The study has found that skilled labor is more sensitive to food tariff reductions than unskilled labor, particularly in rural areas. The results reveal that tariff changes positively affect urban households' welfare, while rural households experience a loss due to these changes. Urban areas benefit from reduced household expenditure, while food prices are increasing in rural areas due to weak or absent tariff pass-through. Although these increases favor producers, they do not compensate for the loss consumers suffer, resulting in reduced welfare in rural areas. The findings show that the effects of tariff changes vary across regions, not only between urban and rural areas but also among different provinces. Furthermore, the tariff reductions have been a boon for consumers, but a bane for producers, ultimately harming production in the long term. The findings suggest that regional markets may be either sufficient or insufficient to convert pass-through-the-border prices into domestic prices. Therefore, policymakers can use this study as a useful guide to reform the regional market structure to raise household welfare, food security, and income inequality.